39 Genomics MDMs need YOU! the changing shape of genomic data interpretation and reporting. (22nd November 2019) - Nutan, Savita; Puvirajasinghe, Clinda; Clement, Emma
Abstract : Genomic testing allows us to screen multiple genes simultaneously via diagnostic panels, exome and genome sequencing. This broad approach has many benefits; however the downside to this approach is the discovery of variants of uncertain significance (VUS). VUS are changes in genes which we are currently unable to classify as likely disease causing or benign. Approximately 36% of variants returned from the 100, 000 genomes project are classified as VUS. National guidelines provide a framework to assist in genomic data interpretation. The cornerstone of this guidance is that ' the genetic change must fit the clinical phenotype' . Additionally, the specificity of the phenotype also adds weight to the interpretation. Clinical-laboratory collaboration is key to accurate reporting and underpins the basis of genomic multidisciplinary meetings (MDMs). Here we discuss cases from the 100, 000 genomes project where clinical input has impacted data interpretation and reporting. Case 1: In a child with delay, hearing impairment and seizures, 2 variants in ACY1 (autosomal recessive aminoacylase 1 deficiency) were identified. One variant was clearly pathogenic, the other a VUS. MDM review confirmed the phenotype to be compatible. Subsequent urine organic acid analysis enabled the second variant to be upgraded establishing a genetic diagnosis. Case 2: A PROM1 splice variant, predicted to cause premature truncation of the protein, was detected in a patient with a clinical diagnosis of macular dystrophy. MDM review revealed that the variant and clinical presentation were not consistent with a dominant inheritance pattern. The variant was hence downgraded preventing a potential misdiagnosis. As genomic testing is embedded in the NHS, it is important for clinicians to understand their crucial role in genomic data interpretation. Understanding when clinical evidence may support or refute a genetic diagnosis is an integral part of care for patients with rare disease.